The Effects Of Different Aeration Rates In The Larval Rearing Of Some Cyprinidae Species - Senoo, Shigeharu (1992)

(untitled)
A study was undertaken t o develop an appropriate technology offish seed production in the tropics in order to overcome the constant water scarcity and its high operational cost . Accordingly , three experiments were carried out at the Fish Hatchery Unit , Faculty of Fisheries and Marine Science, Universiti Pertanian Malaysia to determine the optimum aeration rate and stocking density for fish larval rearing .In the first experiment , one hundred larvae of Puntius gonionotus , Cyprinus carpio , and Carassius auratus were reared for 20 days respectively in tanks with four different aeration rates ; 0,50, 500, and 5,000mL /min . From the results of the first experiment , the aeration rat es of 0 and 5 0 mL / mi n , 5 0 and 500 mL/min , and 50 mL /min were found to be the optimum rates for the larval rearing of Puntius gonionotus , Cyprinus carpio , and Carassius auratus respectively .